2010
DOI: 10.1007/s12517-010-0164-8
|View full text |Cite
|
Sign up to set email alerts
|

Paleostress analysis of the volcanic margins of Yemen

Abstract: The western part of Yemen is largely covered by Tertiary volcanics and is bounded by volcanic margins to the west (Red Sea) and the south (Gulf of Aden). The Oligo-Miocene evolution of Yemen results from the interaction between the emplacement of the Afar plume, the opening of the Red Sea, and the westward propagation of the Gulf of Aden. Structural and microtectonic analyses of fault slip data collected in the field reveal that the volcanic margins of Yemen are affected by three main extensional tectonic even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The maximum vertical displacement of extensional faults is recorded around Sana'a city such as in Haddah fault and reaches to more than 300m. This study is coinciding with several studies of (Al-Kotbah, and Al-Ubaidi, 2001, Al-Ubaidi and Al-kotbah, 2003, Al-Subbary et al, 1998, Khanbari, 2004Khanbari, & 2010. The main trends of faults and fractures measured in current study as shown in Dhudan area (plate 2.A) are coincided and control by the major tectonic elements of Yemen and the rejuvenation of the old regional structures of the Arabian Peninsula.…”
Section: Structuressupporting
confidence: 92%
See 1 more Smart Citation
“…The maximum vertical displacement of extensional faults is recorded around Sana'a city such as in Haddah fault and reaches to more than 300m. This study is coinciding with several studies of (Al-Kotbah, and Al-Ubaidi, 2001, Al-Ubaidi and Al-kotbah, 2003, Al-Subbary et al, 1998, Khanbari, 2004Khanbari, & 2010. The main trends of faults and fractures measured in current study as shown in Dhudan area (plate 2.A) are coincided and control by the major tectonic elements of Yemen and the rejuvenation of the old regional structures of the Arabian Peninsula.…”
Section: Structuressupporting
confidence: 92%
“…At the final stage of volcanic eruption, the Sana'a area was subjected to a compression stage where the Sana'a anticline was formed whose axis trends N-S. This axis dies out in the north with steep plunge in the south, then another stage of extensional faulting resulted which shaped up the present area, and represents an extensional tectonic regime contemporaneous with the opening of Gulf of Aden and the Red Sea (Khanbari and Huchon 2010). This stage produced the most dominant structures where it obscured all old structures.…”
Section: Stratigraphic Sequence In the Sana'a Basinmentioning
confidence: 99%
“…Damt area as a part of Yemen has a prolonged tectonic history started by Neoproterozoic Pan-African orogeny and, ultimately to the ongoing opening of the Gulf of Aden and the Red Sea (Bosworth et al, 2005;As-Saruri et al 2008, andKhanbari, 2015). Therefore, the Damt area is characterized by superimposed tectonic elements represented by numerous fault and fracture populations.…”
Section: Structure Patternmentioning
confidence: 99%
“…3a) reveals that the distribution of the various rock types and geomorphic features appears to be significantly influenced by NNW-SSE, NE-SW and E-W trending normal faults created by extension associated with the opening of the Red Sea and Gulf of Aden [e.g. (39,40)]. The marking of the spatial distribution of the faults was initially achieved by tracing linear elements on ETM+ satellite image and earlier geological maps.…”
Section: Structuresmentioning
confidence: 99%